Investigating the Water-table under Eucalyptus Hybrid by Resistivity Method - Reynolds, E. R. C.; Singhal, R. M.; Pant, S. P. (Indian Forester, 1988)
Hydrologically it is important to distinguish phreatophytic vegetation, as the access to the water-table enables plants to transpire the full potential and not conserve water. However,there is much misunderstanding outside the hydrological discipline on the location and behaviour of the water-table. We describe the methods of wells and electrical resistivity which we have employed in the Terai Eucalyptus plantation to study the water-table, and we discuss the preliminary results which as yet demonstrate little direct abstraction by the trees from water-table deeper than 1.5 metres.